A multidisciplinary approach to managing Ehlers-Danlos (type III) - hypermobility syndrome : working with the chronic complex patient - Knight, Isobel, 1974- (Singing Dragon, 2013)
"The complex effects of Ehlers-Danlos Syndrome (Type 3, Hypermobility), or EDSIII, on a patient's physical and mental wellbeing are extremely challenging for everyone involved, requiring a multidisciplinary care team and enormous dedication from the patient. This book presents an overview of what it means to be a chronic complex patient, examining the wide range of physiological and psychological implications associated with EDSIII and other conditions such as endometriosis and fibromyalgia. It explores the exercise and rehabilitation work involved in managing the condition effectively, considering a diverse range of medical treatments and complementary approaches including physiotherapy, Bowen Technique and Feldenkrais Method(R). There are contributions and insights throughout from experts in the fields of physiotherapy, rheumatology and health psychology, all of whom have extensive experience of working with complex chronic patients. The author links her own symptoms and experiences to those of other EDSIII patients and discusses how she has been able to reach a point where she can successfully manage the condition."--Publisher description